Children's and Parents' Conceptualization of Quality of Life in Children With Brain Tumors: A Meta-Ethnographic Exploration. (January 2019) - Beecham, Emma; Langner, Richard; Hargrave, Darren; Bluebond-Langner, Myra
The concept of quality of life (QoL) is used in consultations to plan the care and treatment of children and young people (CYP) with brain tumors (BTs). The way in which CYP, their parents, and their health care professionals (HCP) each understand the term has not been adequately investigated. This study aimed to review the current qualitative research on CYP, parents' and clinicians' concepts of QoL for CYP with BTs using meta-ethnography. Six studies were found, which reflected on the concept of QoL in CYP with BTs; all explored the CYP's perspective and one study also touched upon parents' concept. A conceptual model is presented. Normalcy (a "new normal") was found to be the key element in the concept. This study calls for a conception of QoL, which foregrounds normalcy over the more common health-related quality of life (HRQoL) and the need to understand the concept from all perspectives and accommodate change over time.